Implementation of Early Childhood Mathematics Learning at PAUDQU Al-Anshor - Gunawan, Marina Trie Ramadhany; Afriliani, Ajeng Teni Nur; Fitri, Dwi Anisak Nurul; Farida, Neng Awalia; Awaliyah, Fitria Nur (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
The introduction of learning mathematics is an important part of early childhood. Mathematics is closely related to human daily life. So that children must be introduced from an early age so that they have adequate mathematical skills in carrying out life in the future. In the field itself, there are many activities to introduce mathematics in early childhood, dominated by calistung activities which are drills and paper pencil tests. The school environment is a place for educators to provide meaningful mathematics learning. Learning mathematics for early childhood should be introduced to various and fun methods. This study uses a type of qualitative research. The study involved 4 teachers and 15 students from groups A and B at PAUDQU Al-Anshor. The results of the study show that the application of early childhood mathematics learning in PAUDQU Al-Anshor does not only use drills and paper pencil tests, but is balanced with various other game activities that can refer to learning mathematics.